El placer en el libro VI de la Ética Eudemia (libro VII de la Ética Nicomáquea). I parte - Solano Fallas, Andrés (2015)
The intention of this article is to elucidate Aristotle’s position on the topic what is pleasure, according to Book VI of Eudemian Ethics (EE) (VII of Nicomachean Ethics), one of the known “common books”. This will be done by an exposition of its characteristics. It is worth noting that the intention of the article takes position against a philosophical tradition that considers this book as part of NE and studies it, most of the times, subordinated to Book X of EN.